Evaluation of the Toxicity and Toxicokinetics of Cereulide from an Emetic Bacillus cereus Strain of Milk Origin - Yifang Cui; Yuan Liu; Xiaoye Liu; Xi Xia; Shuangyang Ding; Kui Zhu (Toxins, 2016)
Bacillus cereus is an opportunistic foodborne agent causing food poisoning and many infectious diseases. The heat-stable emetic toxin cereulide is one of the most prevalent toxins produced by pathogenic B. cereus, resulting in symptoms such as emesis and liver failure. In the present work, the toxicity and toxicokinetics of cereulide from an emetic B. cereus isolate (CAU45) of raw milk were evaluated. The production of cereulide was tested by a cytotoxicity test and enzyme immunoassay, and confirmed by the presence of the ces (cereulide synthetase) gene and the ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method. All results showed that the amount and toxicity of cereulide produced by CAU45 was 7 to 15.3 folds higher than the reference emetic B. cereus DSMZ 4312. Cereulide in plasma was collected at different time points after a single intravenous injection to evaluate its toxicokinetics in rabbits. The maximum concentration of cereulide was achieved in 2.6 ± 3.4 h after administration, with the elimination half-life of 10.8 ± 9.1 h, which expands our understanding of the toxic effects of cereulide. Together, it suggests that urgent sanitary practices are needed to eliminate emetic toxins and emetic B. cereus in raw milk.